Análise espacial dos indicadores de câncer de colo de útero - OLIVEIRA, Jessica Fernanda Galdino (2019)
Cervical cancer is the fourth most common neoplasm in women worldwide. Its prevention can be achieved through cervical cytopathological examination from a screening that allows the detection of lesions and / or early diagnosis of the disease, but there are still a large number of women who do not carry out prevention for numerous factors. The objective of this study was to evaluate the coverage rate of cervical cancer screening (Pap), incidence and mortality from cervical cancer in the state of Para in the period 2006 - 2014. This is an ecological study, with data from the Cervical Cancer Information System – SISCOLO/DATASUS and Cancer Information System – SISCAN, of the entire state of Pará, subdivided into three triennia so that georeferencing techniques were use to. We identified patterns of distribution of the variables studied, where we observed correlations between the rate of the test, the incidence and mortality from cervical cancer. The Marajó mesoregion showed an increase in its coverage rate and incidence and kept its mortality rate stable from the second to the third triennium of study. In the other mesoregions, there was a decrease in the coverage rate of the exam, and the increase in mortality in these localities was observed. The metropolitan mesoregion of Belém was the one that showed the most decline in its coverage rate, becoming the second in a decrease in the incidence of neoplasia, since the Southwest did not show expansion or decrease in its rate of exams performed and was shown to be a greater decrease in incidence and, consequently, a greater increase in the standardized rate of mortality rate. Except for the Marajó and Southwest mesoregions, the pattern found was: decreased Pap coverage, decreased incidence, and increased mortality. Moran 's analysis revealed the expression of pockets of high - high municipalities, mainly in the northeastern mesoregion of the state, which remained in the 3rd triennium, although there was a decrease in incidence and mortality in the region. This study reaffirms the relationship between the coverage and the morbidity and mortality of cervical cancer, since the examination is aimed at early diagnosis and this factor has a direct influence on the reduction of mortality, since there will then be a good time for the treatment and cure of this user. Although the Pará shows values close to what is recommended, in relation to the coverage by the Pap, in domestic areas, access to health makes it difficult to carry out the examination and treatment, due to factors ranging from the lack of health professionals, to lack of knowledge of its importance for the promotion of well-being and prevention against neoplasia in women.